The cancer-testis antigens SPANX-A/C/D and CTAG2 promote breast cancer invasion - Maine, Erin A. (Oncotarget, 2016)
Genes that are normally biased towards expression in the testis are often induced in tumor cells. These gametogenic genes, known as cancer-testis antigens (CTAs), have been extenstively investigated as targets for immunotherapy. However, despite their frequent detection, the degree to which CTAs support neoplastic invasion is poorly understood. Here, we find that the CTA genes SPANX-A/C/D and CTAG2 are coordinately induced in breast cancer cells and regulate distinct features of invasive behavior. Our functional analysis revealed that CTAG2 interacts with Pericentrin at the centrosome and is necessary for directional migration. Conversely, SPANX-A/C/D interacts with Lamin A/C at the inner nuclear membrane and is required for the formation of actin-rich cellular protrusions that reorganize the extracellular matrix. Importantly, SPANX-A/C/D was required for breast cancer cells to spontaneously metastasize to the lung, demonstrating that CTA reactivation can be critical for invasion dependent phenotypes in vivo. Moreover, elevated SPANX-A/C/D expression in breast cancer patient tumors correlated with poor outcome. Together, our results suggest that distinct CTAs promote tumor progression by regulating complementary cellular functions that are integrated together to induce invasive behavior.